SMART ACCOUNTING: AN INNOVATIVE LEARNING MEDIA FOR THE SERVICE ACCOUNTING CYCLE TO ENHANCE STUDENTS’ SELF-DIRECTED LEARNING - Retno Hernawati (Universitas Muhammadiyah Metro, 2026)
This study aims to develop and examine the effectiveness of an Android-based learning media called Smart Accounting on service accounting cycle materials in improving students’ learning independence. The study employed a research and development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were students of the Economic Education Study Program at Nusa Cendana University who were enrolled in the Basic Accounting course. Data were collected through expert validation sheets, learning independence questionnaires, and student response questionnaires. Data analysis techniques included descriptive quantitative analysis, normalized gain analysis, and paired sample t-test. The results indicated that the Smart Accounting learning media was categorized as very feasible based on media and content expert validation. Furthermore, the normalized gain value was 0.56, which falls into the moderate category, and the paired sample t-test results showed a significant difference in students’ learning independence before and after using the learning media. These findings demonstrate that Smart Accounting is effective in improving students’ learning independence on service accounting cycle materials.